Geography and Exporting Behavior : Evidence from India - Mukim, Megha (2012)
This paper examines locational factors that increase the odds of a firm's entry into export markets and affect the intensity of its participation. It differentiates between two different sources of spillovers: clustering of general economic activity and that of export-oriented activity. It also focuses on the effect of the business environment and that of institutions at the spatial unit of districts in India. The study disentangles the within-industry effect from the within-firm effect. A simple logit specification is used to model the probability of entry. The analysis is based on a panel of manufacturing firms in India, which allows for the introduction of firm-specific controls and a battery of fixed effects. The findings suggest that exporter-specific clustering, general economic agglomeration, and institutional factors affect firms' export behavior.